Impact of curricular change on the perception of the educational environment by nursing students - Cerón Mackay, María Consuelo; Garbarini Crisóstomo, Alda; Parro Fluxá, Javiera; Lavín Venegas, Carolina (Investigación y Educación en Enfermería, 2015)
Objective. This study sought to evaluate the impact of curricular change on the perception of the Educational Environment (EE) in nursing students. Methodology. This was a cross-sectional study. Two consecutive cohorts were evaluated during the second year, entering 2010 (N: 58) and 2011 (N: 57) for former and new curriculum, respectively. A sociodemographic survey and perception of the EE was applied through the Dundee Ready Educational Environment Measure (DREEM) questionnaire. Results. No differences were detected in the sociodemographic variables between the cohorts. Both groups evaluated EE more positively than negatively. The total average score of the perception of the EE by the 2010 cohort was of 132 points and by the 2011 cohort of 126 points, a statistically significant difference. Upon analyzing the survey items, it was observed that poorer perception exists of the learning atmosphere and of the social environment, as well as poorer assessment of the academic skills in the 2011 cohort compared to the 2010 cohort. The good preparation the students are receiving for the profession and the relevance of the assignments they are learning are considered strengths by the students from both groups. Conclusions. In spite of how positive the curricular changes could seem, perception of the EE in both cohorts does not reach the excellent category. Before any changes are made to the curriculum, it is indispensable to take into account how the academic load might affect the students. How to cite this article: Cerón MC, Garbarini A, Parro J, Lavín C. Impact of curricular change on the perception of the educational environment by nursing students. Invest Educ Enferm. 2015; 33(1)…